Knowledge of contraceptive use among adolescent girls and young women aged 10 - 24 years at Kiyindi landing site, Buikwe district, Uganda. A cross-sectional study. - Wamala, Amir; Mabonga, Herbert; Nalubega, Joy (Student’s Journal of Health Research Africa, 2026)
Background There have been several other efforts targeting adolescent girls and young women to foster their behavioural change by way of improving their knowledge, attitudes, and practices of contraceptive use. The objective of the study was to assess the knowledge of contraceptive use among AGYW (10-24Years) at Kiyindi landing site. Methodology A descriptive cross-sectional study design was used with quantitative methods of data collection. Data was entered and analysed using Stata statistical software version MP 14.0, Stata Corporation. Descriptive statistics were used for bivariate and multivariate logistic regression analysis. Results More than half of the respondents (55.7%, N = 377) were aged between 20 and 24 years. Bivariate Analysis of knowledge about contraception and Use by Respondents showed that Knowledge about the importance of leaving a space at the tip when putting on a condom (ꭓ2=54.887, p-value of .000), importance of the man to pull out right after ejaculation when using a condom (X2=21.073, p-value of .000), wearing two latex condoms to provide extra protection (ꭓ2=3.486, p-value of .041), Women “taking a break” from the pill every couple of years (ꭓ2=8.277, p-value of 0.003), women switching to another type or brand of pill when having side effects with one kind of pill, (ꭓ2=3.896, p-value of .032), a woman having a pelvic exam as a must in order to get a birth control pill (ꭓ2=4.743, p-value of .020), and a woman using an IUD even if she had never had a child (ꭓ2=4.135, p-value of .029) were significantly associated with respondents’ use of contraception. Conclusions Respondents were found to be moderately knowledgeable about contraception Recommendations Health workers should teach the community about family planning holistically to increase awareness, so that family planning utilization will be enhanced